Phylogenetic and Morphological Analyses Reveal Twelve New Species of the Genus Patellaria (Dothideomycetes, Ascomycota) from Mexico - Ilian García-Jacobo; Tania Raymundo; Cesar R. Martínez-González; Michelle Martínez-Pineda; Ricardo Valenzuela (Journal of Fungi)
Patellaria species are widely distributed in terrestrial and marine habitats and are saprobes growing on decaying wood, stems, or bark. However, studies on this genus in Mexico are limited, and only the type species Patellaria atrata Fr. has been cited. This study describes twelve new Patellaria species in Mexico supported by molecular (ITS-LSU-SSU) and morphological data. Phylogenetic analysis shows that species of this genus in Mexico are not closely related to Patellaria atrata. Moreover, the results demonstrate that the greatest species diversity is found in dry climates, particularly in xerophilous scrub.